A B-free atmospheric pressure sintered high-purity SiC and its application
Through the normal pressure solid phase sintering method, combining the mixture of α-SiC and β-SiC powders and the sintering additive of polymers, the problem of achieving high-purity and high-density SiC ceramics without adding B-containing additives is solved, and the SiC ceramics with high purity and high density are achieved at a lower sintering temperature, which is suitable for semiconductor fields.
Patent Information
- Application Number
- CN202510000140.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-02
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2045-01-02
AI Technical Summary
The prior art is difficult to achieve sintering of high-purity, high-density SiC ceramics without adding B-containing sintering aids, especially at lower sintering temperatures.
By using the normal pressure solid phase sintering method, by mixing α-SiC and β-SiC powders, and adding polymers with silicon-carbon atom ratio of 0.95 to 1.05 as sintering aid, the modification liquid is treated and sintered, avoiding the introduction of foreign impurities and maintaining high purity and high density.
At a lower sintering temperature (1700~2200℃), high purity (≥99.9%) and high density SiC ceramics were successfully obtained, which improved the performance of the material and was suitable for the high purity requirements in the semiconductor field.
Smart Images

Figure CN119390452B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a B-free, normal pressure sintered high-purity SiC ceramic material and application thereof, belonging to the technical field of high-purity and dense ceramic development. Background Art
[0002] In China's third-generation silicon carbide semiconductor industry, the chip manufacturing link occupies a core position. The various devices needed in silicon carbide semiconductor processing are the key to affecting my country's third-generation silicon carbide semiconductor industry. Among them, high-purity silicon carbide (SiC) materials, due to their many excellent properties, such as high strength, hardness, rigidity, chemical stability, excellent oxidation resistance and wear resistance, account for a large proportion of the prepared devices. Currently, SiC ceramic devices widely used in semiconductor processing are mainly prepared by recrystallization sintering. Although recrystallized SiC has extremely high purity and does not contain any metal phase and glass phase, it has low density and strength. With the further development of the semiconductor industry, the performance of recrystallized SiC ceramic devices can no longer meet the requirements of larger wafer processing.
[0003] At present, the preparation of high-purity SiC ceramic materials is mainly achieved by hot pressing sintering or spark plasma sintering. Although the above processes can prepare high-density SiC ceramics without adding sintering aids, the sintering conditions are relatively harsh. Both methods are not suitable for the preparation of large-sized and complex-shaped ceramic parts, and the preparation cycle is long and not suitable for mass production.
[0004] Previous studies at home and abroad have shown that dense SiC ceramics can be prepared by adding B-containing sintering aids through solid phase sintering at normal pressure, but the residual B element in the obtained ceramics is more than 0.3%. In the subsequent heat treatment of SiC wafers, the volatilization of B element under high temperature conditions poses a risk of seriously contaminating high-value SiC wafers, such as patents GB1478898A and US4312954A. Therefore, the idea of sintering high-purity SiC ceramics by adding B-containing sintering aids has been gradually abandoned by the industry. Summary of the invention
[0005] Based on the difficulty of densifying SiC ceramics without adding B-containing sintering aids, the present invention attempts for the first time to obtain high-purity and high-density SiC ceramics at a lower sintering temperature without introducing boron.
[0006] The present invention adopts normal pressure solid phase sintering of β-SiC and α-SiC mixed powders, and achieves the molding and sintering requirements of high-purity SiC ceramics required for semiconductor processing applications by adding a relatively low content of a specific sintering aid.
[0007] The invention discloses a B-free, normal pressure sintered high-purity SiC ceramic material. The material comprises alpha-SiC powder and beta-SiC powder as raw materials, the raw material powder is added into a modified liquid, the material is uniformly stirred, dried, pressed into shape, and sintered under a protective atmosphere to obtain a high-purity SiC ceramic. The modified liquid contains a sintering aid, which is a high molecular polymer with a silicon-carbon atomic ratio of 0.95-1.05. The amount of the sintering aid is 8-25% of the mass of the raw material powder. The sintering temperature under the protective atmosphere is 1700-2200°C. The mass percentage of SiC in the obtained high-purity SiC ceramic is greater than or equal to 99.9%.
[0008] The invention discloses a B-free, pressure-sintered, high-purity SiC ceramic material; the mass ratio of the α-SiC powder to the β-SiC powder is 50-95:5-50, preferably 55-95:5-45, more preferably 58-75:7-18, and even more preferably 60-75:14-17. The amount of the α-SiC powder is preferably greater than that of the β-SiC powder.
[0009] The present invention preferably prefers that the amount of α-SiC powder is greater than the amount of β-SiC powder because α-SiC powder has higher thermal stability and high temperature resistance, and can maintain good stability during high temperature sintering, while β-SiC will transform into α-SiC under high temperature conditions, and its sintering performance is poor, and it is difficult to achieve high density. The transformation of a small amount of β-SiC to α-SiC will lead to the elongation of secondary α-SiC grains, thereby significantly improving the mechanical properties of SiC ceramics. When applied in industry, the purpose of such preference is to improve the strength and density of the final sintered high-purity silicon carbide ceramics to meet its application scenarios.
[0010] Preferably, the purity of the α-SiC powder is ≥99.99% and the particle size is 20-120 μm.
[0011] Preferably, the purity of β-SiC powder is ≥99.99% and the particle size is 10-20μm. When used in industry, the particle size of α-SiC powder used is larger than that of β-SiC powder used. The advantage of this choice is that the use of large-particle α-SiC helps to form a more uniform microstructure, avoids brittleness and cracks caused by too small particle size, and improves the strength and mechanical properties of the final silicon carbide ceramic.
[0012] The solvent of the modified liquid is an organic solution, which is composed of xylene and polyvinyl butyral (PVB), wherein the amount of polyvinyl butyral (PVB) added is 1-5wt% of the raw material, and the amount of xylene added is 5-15%, preferably 9-13% of the raw material.
[0013] The sintering aid added to the modified liquid is 8.5-20wt% of the mass of the raw material used, preferably 8.5-15%.
[0014] The added sintering aid is selected from at least one of polycarbosilane, polymethylsilane, polysiloxane and polysilazane.
[0015] Add the raw material powder into the modified liquid, stir evenly, and dry at 80-100℃ for 30min~60min.
[0016] During pressing, the pressure is controlled at 30-50MPa.
[0017] During sintering, the protective atmosphere used is selected from at least one of argon and vacuum.
[0018] During sintering, the sintering temperature is controlled to be 1700-2200°C and the sintering time is 60-120 minutes. This sintering temperature range certainly includes small ranges such as 1700-1800°C, 1700-1900°C, 1800-1900°C, 1700-2000°C, 1800-2100°C, etc. The present invention can obtain high-purity and dense silicon carbide at a lower sintering temperature (such as 1700-1800°C).
[0019] When used in industry, after obtaining high-purity SiC ceramics, the obtained high-purity SiC ceramics can also be placed in a xylene solution containing polycarbosilane, and then vacuum-impregnated and dried, and then heated to 1200-1500°C at a heating rate of 5-20°C / min and kept warm for 0.5-3h; the impregnation, drying and sintering are repeated 3-20 times, preferably 9-15 times to obtain the re-fired high-purity SiC ceramics.
[0020] In order to further improve the performance, the obtained re-fired high-purity SiC ceramics were used as the treatment object, trichloromethylsilane was used as the Si source and C source, hydrogen and argon were used as the carrier gas and dilution gas, and SiC coating was prepared on its surface at 1000-1200°C to obtain re-fired high-purity SiC ceramics with deposited silicon carbide coating on the surface.
[0021] When used in industry, after obtaining high-purity SiC ceramics or re-fired high-purity SiC ceramics, laser precision processing and diamond grinding can be used to remove burrs and potholes at corners.
[0022] The obtained product is used in the semiconductor field, specifically as a SiC wafer holder and tooling in the semiconductor industry. The product is selected from at least one of the obtained high-purity SiC ceramic, the obtained refired high-purity SiC ceramic, and the obtained refired high-purity SiC ceramic with a deposited silicon carbide coating on the surface.
[0023] Principles and advantages
[0024] Principle of the invention:
[0025] Traditional sintering methods often use B sintering aids to promote sintering densification, but these aids will inevitably introduce impurities into the material and reduce the purity of the ceramic. The present invention, by appropriately matching raw materials and using a high molecular polymer (preferably polycarbosilane) with a silicon-carbon atomic ratio of 0.95 to 1.05 as a sintering aid, avoids the introduction of foreign impurities through a normal pressure sintering method, maintains the high purity and high density of silicon carbide ceramics, and greatly improves the performance of the material. The resulting product is particularly suitable for the semiconductor field with extremely high purity requirements.
[0026] Advantages of the present invention:
[0027] 1. The sintering of high-purity SiC ceramics can be achieved without adding sintering aids containing B elements and without reaction sintering.
[0028] 2 No impurities other than Si and C elements will be introduced.
[0029] 3 There is no volatile phase under high temperature conditions. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 The macroscopic morphology of the SiC green body before and after sintering in Example 1;
[0031] Figure 2 This is a microscopic morphology of the SiC green body after the initial sintering in Example 1;
[0032] Figure 3 is the XRD diffraction pattern of the SiC green body after sintering in Example 1;
[0033] Figure 4 The macroscopic morphology of the SiC green body before and after sintering in Example 2;
[0034] Figure 5 This is a microscopic morphology of the SiC green body after sintering in Example 2;
[0035] Figure 6 This is the EDX spectrum of the SiC green body after the initial sintering in Example 2;
[0036] Figure 7 This is a physical picture of the product obtained by chemical vapor deposition in Example 6;
[0037] Figure 8 This is a microscopic morphology of the coating in the product obtained by chemical vapor deposition in Example 6;
[0038] Fig. 9 This is the XRD diffraction pattern of the coating in the product obtained by chemical vapor deposition in Example 6.
[0039] Figure 1 It consists of two pictures (a) and (b), where (a) is a real picture of the green body before sintering; (b) is a real picture of the silicon carbide ceramic obtained after sintering; Figure 1 It can be seen that after the green body is pressed, the surface is smooth and flat, with no obvious cracks or peeling. After the green body is sintered, the surface is smooth and dense, with no obvious cracks or peeling.
[0040] from Figure 2 It can be seen that after the first sintering of the green body, there was no subsequent impregnation-cracking-sintering. The green body was dense after sintering, with uniform grain size and no obvious cracks in the block.
[0041] from Figure 3 It can be seen that only SiC ceramic phase appears after sintering, without other impurity peaks.
[0042] Figure 4 It consists of two pictures (a) and (b), where (a) is a real picture of the green body before sintering; (b) is a real picture of the silicon carbide ceramic obtained after sintering; Figure 4 It can be seen from the figure that after the first sintering of the green body, there is no subsequent impregnation-cracking-sintering. After the green body is pressed and formed, the surface is smooth and flat, with no obvious cracks and no obvious peeling. After the green body is sintered, the surface is smooth and dense, with no obvious cracks and no obvious peeling.
[0043] from Figure 5 It can be seen that the billet is denser after sintering, the grain size is uniform, and there are no obvious cracks in the block.
[0044] from Figure 6 It can be seen that only Si and C peaks appear after sintering, without other impurity elements.
[0045] from Figure 7 It can be seen that the SiC coating is flat and smooth and evenly distributed on the ceramic block.
[0046] from Figure 8 It can be seen that the grain size of the SiC coating is uniform and no obvious voids are formed.
[0047] from Fig. 9 It can be seen that only SiC peak appears in the coating, without other impurity elements. DETAILED DESCRIPTION
[0048] Example 1
[0049] Commercial α-SiC powder (purity ≥ 99.99%, particle size 20-120 μm) and β-SiC powder (purity ≥ 99.99%, particle size 10-20 μm) are used as raw materials, and the mass ratio of α-SiC powder to β-SiC powder in the raw materials is 65:15; the raw materials are added into a xylene solution containing polycarbosilane and a polyvinyl butyral (PVB) solution, mixed, and SiC slurry is obtained by mechanical stirring; in the slurry, the mass percentage of the raw material powder is 80wt%, the mass percentage of the polycarbosilane is 7wt%, the mass percentage of the xylene is 10wt%, and the mass percentage of the polyvinyl butyral (PVB) is 3wt%;
[0050] (2) pouring the obtained SiC slurry into a metal mold, drying it at 90° C. for 30 minutes, and pressing it at 30 MPa to obtain a SiC body;
[0051] (3) placing the obtained SiC body in an inert atmosphere of argon gas, and performing pressureless sintering at 1700° C. for 60 minutes to obtain the high-purity SiC ceramic;
[0052] (4) The SiC ceramic is subjected to laser precision machining and diamond grinding to remove burrs and potholes at corners.
[0053] (5) The SiC ceramic is placed in a xylene solution containing high-purity polycarbosilane (the mass ratio of high-purity polycarbosilane to xylene is 4:6), and then vacuum-impregnated and dried, and then heated to 1400° C. at a heating rate of 5° C. / min and kept warm for 0.5 h.
[0054] (6) Repeat the process in (5) above for 15 times. Then, the obtained sample is diamond polished and cleaned.
[0055] The density of the high-purity SiC ceramic obtained in step (3) is 2.47 g cm -3 After the process in (5) was repeated 15 times, the density of the high-purity SiC ceramic obtained in step (6) was 3.09 g·cm -3 .
[0056] The maximum shrinkage in each direction before and after sintering is 0.09%.
[0057] The mechanical properties of the high-purity SiC ceramic finally obtained are 310±25MPa. The high-purity SiC ceramic can be used as a SiC wafer support and tooling in the semiconductor industry.
[0058] Example 2
[0059] The other conditions are the same as those in Example 1, except that: in step (3), the obtained SiC body is placed in an inert atmosphere of argon gas and kept at 2200° C. for 120 minutes for pressureless sintering to obtain the high-purity SiC ceramic;
[0060] The density of the high-purity SiC ceramic obtained in step (3) is 2.36 g cm -3 After the process in (5) was repeated 9 times, the density of the high-purity SiC ceramic obtained in step (6) was 2.73 g·cm -3 The maximum shrinkage in each direction before and after sintering is 0.12%. The mechanical properties of the obtained high-purity SiC ceramics are 250±20MPa.
[0061] Example 3
[0062] The other conditions are the same as those in Example 1, except that: in step (3), the obtained SiC body is placed in an inert atmosphere of argon gas and kept at 1950° C. for 60 minutes for pressureless sintering to obtain the high-purity SiC ceramic;
[0063] The density of the high-purity SiC ceramic obtained in step (3) is 2.34 g·cm-3; after the process in the above (5) is repeated 9 times, the density of the high-purity SiC ceramic obtained in step (6) is 2.71 g·cm -3 The maximum shrinkage rate in each direction before and after sintering is 0.12%. The mechanical properties of the obtained high-purity SiC ceramics are 255±23MPa.
[0064] Example 4
[0065] The other conditions are the same as those in Example 1, except that: in step (1), commercial α-SiC powder (purity ≥ 99.99%, particle size 20-120 μm) and β-SiC powder (purity ≥ 99.99%, particle size 10-20 μm) are used as raw materials, and the mass ratio of α-SiC powder to β-SiC powder in the raw materials is 75:15; the raw materials are added into a xylene solution containing polycarbosilane and a polyvinyl butyral (PVB) solution, and a SiC slurry is obtained by mechanical stirring; in the slurry, the mass percentage of the raw material powder is 80wt%, the mass percentage of polycarbosilane is 7wt%, the mass percentage of xylene is 10wt%, and the mass percentage of polyvinyl butyral (PVB) is 3wt%;
[0066] The density of the high-purity SiC ceramic obtained in step (3) is 2.42 g·cm -3 After the process in (5) was repeated 14 times, the density of the high-purity SiC ceramic obtained in step (6) was 2.95 g·cm -3The maximum shrinkage in each direction before and after sintering is 0.10%. The mechanical properties of the obtained high-purity SiC ceramics are 300±25MPa.
[0067] Example 5
[0068] The other conditions are the same as those in Example 1, except that: in step (1), commercial α-SiC powder (purity ≥ 99.99%, particle size 20-120 μm) and β-SiC powder (purity ≥ 99.99%, particle size 10-20 μm) are used as raw materials, and the mass ratio of α-SiC powder to β-SiC powder in the raw materials is 55:15; the raw materials are added into a xylene solution containing polycarbosilane and a polyvinyl butyral (PVB) solution, and a SiC slurry is obtained by mechanical stirring; in the slurry, the mass percentage of the raw material powder is 80wt%, the mass percentage of polycarbosilane is 7wt%, the mass percentage of xylene is 10wt%, and the mass percentage of polyvinyl butyral (PVB) is 3wt%;
[0069] The density of the high-purity SiC ceramic obtained in step (3) is 2.40 g·cm -3 After the process in (5) was repeated 10 times, the density of the high-purity SiC ceramic obtained in step (6) was 2.84 g·cm -3 The maximum shrinkage in each direction before and after sintering is 0.11%. The mechanical properties of the obtained high-purity SiC ceramics are 280±15MPa.
[0070] Example 6
[0071] The other conditions were consistent with those in Example 1, except that: the steps of Example 1 were repeated, and the obtained SiC high-purity ceramic was placed in a vacuum tube furnace, trichloromethylsilane was used as the Si source and C source, hydrogen and argon were used as the carrier gas and dilution gas, the molar ratio of trichloromethylsilane, hydrogen and argon was 1.0:4.0:2.5, the flow rate was 20 mL / min, and the SiC coating was prepared at 1000°C.
[0072] Example 7
[0073] The other conditions were the same as those in Example 1, except that an equal amount of polymethylsilane was used instead of polycarbosilane.
[0074] The maximum shrinkage in each direction before and after sintering is 0.10%.
[0075] The mechanical property of the high-purity SiC ceramic finally obtained is 300±18MPa. The high-purity SiC ceramic can be used as a SiC wafer support and tooling in the semiconductor industry.
[0076] Example 8
[0077] The other conditions were the same as those in Example 1, except that an equal amount of polysiloxane was used instead of polycarbosilane.
[0078] The maximum shrinkage in each direction before and after sintering is 0.09%.
[0079] The mechanical properties of the high-purity SiC ceramic finally obtained are 320±20MPa. The high-purity SiC ceramic can be used as a SiC wafer support and tooling in the semiconductor industry.
[0080] Example 9
[0081] The other conditions were the same as those in Example 1, except that an equal amount of polysilazane was used instead of polycarbosilane.
[0082] The maximum shrinkage in each direction before and after sintering is 0.01%.
[0083] The mechanical properties of the high-purity SiC ceramic finally obtained are 330±10MPa. The high-purity SiC ceramic can be used as a SiC wafer support and tooling in the semiconductor industry.
[0084] Comparative Example 1
[0085] The other conditions are the same as those in Example 1, except that: in step (1), commercial α-SiC powder (purity ≥ 99.99%, particle size 20-120 μm) and β-SiC powder (purity ≥ 99.99%, particle size 10-20 μm) are used as raw materials, and the mass ratio of α-SiC powder to β-SiC powder in the raw materials is 65:15; the raw materials are added into a xylene solution and a polyvinyl butyral (PVB) solution, and a SiC slurry is obtained by mechanical stirring, wherein the mass percentage of the raw material powder is 80 wt %, the mass percentage of xylene is 15.4 wt %, and the mass percentage of polyvinyl butyral (PVB) is 4.6 wt %;
[0086] The density of the SiC ceramic obtained in step (3) is only 2.14 g·cm -3 The maximum shrinkage in each direction before and after sintering is 0.23%. The mechanical properties of the obtained SiC ceramics are 80±15MPa.
[0087] Comparative Example 2
[0088] The other conditions are the same as those in Example 1, except that: in step (1), commercial α-SiC powder (purity ≥ 99.99%, particle size 20-120 μm) is used as raw material; the raw material is added into a xylene solution containing polycarbosilane and a polyvinyl butyral (PVB) solution, and a SiC slurry is obtained by mechanical stirring; in the slurry, the mass percentage of the raw material powder is 80wt%, the mass percentage of the sintering aid is 7wt%, the mass percentage of xylene is 10wt%, and the mass percentage of polyvinyl butyral (PVB) is 3wt%;
[0089] The density of the SiC ceramic obtained in step (3) is only 2.32 g·cm -3 The maximum shrinkage in each direction before and after sintering is 0.13%. The mechanical properties of the obtained SiC ceramics are 85±20MPa.
[0090] Comparative Example 3
[0091] The other conditions are the same as those in Example 1, except that: in step (1), commercial β-SiC powder (purity ≥ 99.99%, particle size 10-20 μm) is used as raw material; the raw material is added into a xylene solution containing polycarbosilane and a polyvinyl butyral (PVB) solution, and a SiC slurry is obtained by mechanical stirring; in the slurry, the mass percentage of the raw material powder is 80wt%, the mass percentage of the sintering aid is 7wt%, the mass percentage of xylene is 10wt%, and the mass percentage of polyvinyl butyral (PVB) is 3wt%;
[0092] The density of the SiC ceramic obtained in step (3) is only 1.97 g·cm -3 The maximum shrinkage in each direction before and after sintering is 0.34%. The mechanical properties of the obtained SiC ceramics are 30±12MPa.
Claims
1. A B-free, pressure-sintered high-purity SiC ceramic material, characterized in that: Using α-SiC powder and β-SiC powder as raw materials, adding the raw material powder into the modified liquid, stirring evenly, drying, and then pressing into shape and sintering under a protective atmosphere to obtain high-purity SiC ceramics; the modified liquid contains a sintering aid, and the sintering aid is a high molecular polymer with a silicon-carbon atomic ratio of 0.95 to 1.05; the sintering temperature under the protective atmosphere is 1700 to 2200° C., and the sintering aid is selected from at least one of polycarbosilane, polymethylsilane, polysiloxane, and polysilazane; The mass ratio of the α-SiC powder and the β-SiC powder used is α-SiC powder: β-SiC powder = 50-95: 5-50, and the amount of the α-SiC powder used is greater than the amount of the β-SiC powder used; The purity of α-SiC powder is ≥99.99%, and the particle size is 20-120μm; The purity of β-SiC powder is ≥99.99%, and the particle size is 10-20μm; the particle size of the α-SiC powder used is larger than that of the β-SiC powder used; The sintering aid added to the modified liquid is 8-25wt% of the mass of the raw materials used.
2. The pressureless sintered high-purity SiC ceramic material without B according to claim 1, characterized in that: The mass ratio of the α-SiC powder and β-SiC powder used is α-SiC powder: β-SiC powder = 58~75:7~18.
3. The pressureless sintered high-purity SiC ceramic material without B according to claim 1, characterized in that: The solvent of the modified liquid is an organic solution, which is composed of xylene and polyvinyl butyral ester, wherein the amount of polyvinyl butyral ester added is 1-5wt% of the raw material; the amount of xylene added is 5-15% of the raw material; The sintering aid added to the modified solution is 8.5-20wt% of the mass of the raw materials used.
4. The pressureless sintered high-purity SiC ceramic material without B according to claim 1, characterized in that: Add the raw material powder into the modified liquid, stir evenly, and dry at 80-100℃ for 30min~60min; During pressing, the pressure is controlled at 30-50MPa; During sintering, the protective atmosphere used is selected from at least one of argon and vacuum; During sintering, the sintering temperature is controlled to be 1700~2200°C and the sintering time is controlled to be 60~120 minutes.
5. The pressureless sintered high-purity SiC ceramic material without B according to claim 1, characterized in that: After obtaining the high-purity SiC ceramic, the high-purity SiC ceramic is placed in a xylene solution containing polycarbosilane, and then vacuum-impregnated and dried, and then heated to 1200-1500°C at a heating rate of 5-20°C / min and kept warm for 0.5-3h; the impregnation, drying and sintering are repeated 3-20 times to obtain the re-fired high-purity SiC ceramic.
6. The pressureless sintered high-purity SiC ceramic material without B according to claim 5, characterized in that: The obtained double-fired high-purity SiC ceramic is used as the treatment object, trichloromethylsilane is used as the Si source and C source, hydrogen and argon are used as the carrier gas and the dilution gas, and a SiC coating is prepared on its surface at 1000-1200°C to obtain a double-fired high-purity SiC ceramic with a deposited silicon carbide coating on the surface.
7. An application of the pressureless sintered high-purity SiC ceramic material without B as claimed in any one of claims 1 to 6, characterized in that: The obtained product is used in the semiconductor field, and the product is selected from at least one of the obtained high-purity SiC ceramics, the obtained double-fired high-purity SiC ceramics, and the obtained double-fired high-purity SiC ceramics with a deposited silicon carbide coating on the surface.
Citation Information
Patent Citations
Sintered silicon carbide ceramic body
US4312954A
SiC bonded ceramic matrix composite material and preparation method thereof
CN104177113A
Preparation method of SiCf / SiC composite material with SiC coating layer
CN109400169A